Biodiversity and climate change : transforming the biosphere - Lovejoy, Thomas E.; Hannah, Lee Jay; Wilson, Edward O. (Yale University Press, 2019)
An essential, up-to-date look at the critical interactions between biological diversity and climate change that will serve as an immediate call to action The physical and biological impacts of climate change are dramatic and broad-ranging. People who care about the planet and manage natural resources urgently need a synthesis of our rapidly growing understanding of these issues. In this all-new sequel to the 2005 volume Climate Change andBiodiversity, leading experts in the field summarize observed changes, assess what the future holds, and offer suggested responses. Edited by distinguished conservationist Thomas E. Lovejoy and climate change biologist Lee Hannah, this comprehensive volume includes the latest research and explores emerging topics. From extinction risk to ocean acidification, the future of the Amazon to changes in ecosystem services, and geoengineering to the power of ecosystem restoration, this volume captures the sweep of climate change transformation of the biosphere. An authoritative, up-to-date reference, this is the new benchmark synthesis for climate change scientists, conservationists, managers, policymakers, and educators.